The economics of geographically differentiated agri-food products : Theoretical considerations and empirical evidence - Teuber, Ramona; Justus Liebig University Giessen (My University, 2010)
Geographical names for agri-food products and particularly the legal protection of those names are discussed more than ever. The reasons for this recent interest are manifold. First, an increasing consumer segment is concerned about food safety and food quality issues and thus wants to know where the food they eat comes from. Second, from a policy point of view it is assumed that the protection and promotion of geographically differentiated agri-food products (GDAFPs) can foster rural development. For the European Commission, geographically differentiated products even constitute one main pillar of the EU s agricultural quality policy besides organic and other food quality certification schemes. Against this background, the dissertation provides a comprehensive picture of the eco-nomic aspects of geographically differentiated agri-food products in general, while at the same time presenting very specific results for certain products and markets.The first section introduces major research questions discussed in the context of GDAFPs and provides a comprehensive review and assessment of the economic analysis of these products. Section II presents results from two consumer studies carried out in Germany. The first study analyses consumers preferences for regional food in general, whereas the second one addresses the protection of Hessian Apple wine as a geographical indication in particular. In both studies logit models based on survey data are estimated. The obtained results indicate that psychographic factors such as the wish to support domestic producers are central deter-minants of consumers preferences and willingness to pay for GDAFPs, whereas sociodemo-graphic and economic factors do not possess much explanatory power. Section III provides empirical evidence with respect to the importance of country- and region-of-origin effects in the price formation of single-origin coffees. All four articles in this section are closely linked with each other. The econometric results highlight that coffees from origins without any established reputation for high quality are discounted even after having controlled for sensory quality differences. These significant origin effects can be interpreted as collective reputation effects, a phenomenon well known for wine. Methodologically section III contributes to the exisiting scientific literature by (i) analysing how a two-stage hedonic model can be specified according to the available data set and (ii) providing an empirical application for single-origin coffee data consisting of nonlinear hedonic price functions at stage one and an inverse demand function for sensory quality at stage two.

Obwohl die Herkunft schon lange in der Produktkennzeichnung von Lebensmitteln verwandt wird, ist das Interesse an so genannten geschützten Herkunftsangaben insbesondere in den letzten Jahren erheblich angestiegen. Gründe hierfür sind unter anderem das zunehmende Interesse der Verbraucher an Herkunft und Authentizität von Lebensmitteln, aber auch der Wandel in den Instrumenten der Agrarpolitik hin zur Förderung von Qualitätsprodukten. Die vorliegende kumulative Dissertation greift diese aktuellen Entwicklungen auf und liefert neben einem umfassenden Forschungsrahmen für die ökonomische Analyse geographisch differenzierter Agrarprodukte empirische Ergebnisse für spezifische Märkte. Im ersten Kapitel wird ein umfassender Literatur- und Methodenüberblick geliefert und die wichtigsten Forschungsfragen im Kontext geographisch differenzierter Produkte erläutert. Die zwei folgenden Kapitel beinhalten empirische Studienergebnisse. Kapitel 2 beleuchtet die Konsumentenseite und enthält zwei Studien zu regionalen Lebensmitteln im Allgemeinen und dem Herkunftsschutz für Hessischen Apfelwein im Speziellen. Beide Studien basieren auf Befragungsdaten, welche mit Hilfe von Logit-Modellen ökonometrisch ausgewertet wurden. Die Ergebnisse zeigen, dass für deutsche Verbraucher insbesondere psychographische Faktoren wie die Unterstützung der heimischen Wirtschaft wichtig für das Vorliegen einer Präferenz bzw. Zahlungsbereitschaft für solche Produkte sind. Soziodemografische sowie ökonomische Faktoren liefern dahingegen nur einen sehr geringen Erklärungsbeitrag.Kapitel 3 besteht aus vier miteinander verbundenen Studien zum Spezialitätenkaffeemarkt. Die Etablierung von geschützten Herkunftsangaben hat gerade im Kaffeemarkt in den letzten Jahren stark zugenommen und die vier Beiträge widmen sich unterschiedlichen Aspekten dieser Entwicklung. Zentrale inhaltliche Erkenntnisse dieser Untersuchungen sind, dass signifikante Herkunftseffekte sowohl auf Länder- als auch Regionenebene bestehen, wobei Kaffee aus Guatemala ceteris paribus jeweils die höchsten Preise erzielt. Methodisch leistet die Dissertation einen Beitrag durch (i) die Analyse der möglichen Ansätze ein zweistufiges hedonisches Modell zu spezifizieren und zu schätzen und (ii) die empirische Schätzung eines solchen Modells bestehend aus nichtlinearen hedonischen Preisfunktionen auf der ersten Stufe und einer inversen Nachfragefunktion für sensorische Qualität auf der zweiten Stufe.
Ökonomische Aspekte geographisch differenzierter Agrarprodukte : Theoretische Überlegungen und Empirische Evidenz
Keywords: geschützte Herkunftsangaben; Spezialitätenkaffee; Hessischer Apfelwein; hedonische Preisanalysen; geographical indications; single-origin coffee; Hessian apple wine; hedonic price analyses; ddc:330